The effect of real estate speculation on the growth of economics in Lithuania - Simanaviсiene, Zaneta; Sliupas, Rokas (Економічний вісник Донбасу, 2010)
European countries with transition economies are suffering from unemployment and fluctuating prices, now being plagued by rampant real estate bubble. One of the major social and economic problems in recent years has been the sustained real estate price spiral. The excessively high real estate price means worsening affordability, mortgage payment defaults and impacts the economy’s growth. Present real estate boom is an archfiend wielding terrible power, capable of blowing out the flickering signs of a hopeful economic recovery. It is a common belief that the presence of bubbles in real estate price did impact on the economy and usually caused by speculative activities. Countries, wishing to reduce recession or prevent financial crisis, have to monitor and supervise the real estate market. This paper is designed to evaluate the contribution of speculative activities to real estate price hike. An empirical model is presented that allows for decomposition of house price appreciation into that driven by economic and demographic forces and that resulting from speculative demand. Lithuania is taken as an example of transition country due to its unique historical and financial situation. Main conclusion is that slowdown of accumulation in real estate market and slowed down growth in construction sector leads to real estate market recession as well as to economic slowdown. Key words: real estate speculation, real estate price bubble, real estate market crisis. Європейські країни з перехідними економіками страждають від безробіття та коливань цін на нерухоме майно. Однією з головних соціальних і економічних проблем останніми роками була спіраль цін нерухомого майна. Надмірно висока ціна на нерухоме майно передбачає погіршення купівельної спроможності та впливає на зростання економіки. Стаття присвячена оцінюванню внеску спекулятивних дій ціни нерухомого майна. Литва розглядається як приклад країни з перехідною економікою. Ключові слова: спекуляції нерухомим майном, міхур ціни нерухомого майна, криза ринку нерухомого майна. Европейские страны с экономиками перехода страдают от безработицы и колебаний цен на недвижимое имущество. Одной из главных социальных и экономических проблем в последние годы была спираль цен недвижимого имущества. Чрезмерно непомерная цена недвижимого имущества подразумевает ухудшение покупательной способности и воздействует на рост экономики. Статья посвящена оценке вклада спекулятивных действий цены недвижимого имущества. Литва рассматривается как пример страны с переходной экономикой. Ключевые слова: спекуляции недвижимым имуществом, пузырь цены недвижимого имущества, кризис рынка недвижимого имущества.